1962
DOI: 10.1161/01.res.10.5.753
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tourniquet Shock and Acute Hemorrhage on the Circulation of Various Organs in the Rat

Abstract: Cardiac output, blood pressure, and organ fractions of cardiac output, except the brain, were determined in rats subjected to tourniquet shock and to hemorrhage. Bleeding involved the withdrawal of 23 and 32 ml./Kg. blood, respectively, and determinations were carried out 5 to 20 minutes after bleeding. Sapirstein's "indicator fractionation" method with Rb 86 was used for the determination of the cardiac output fractions. Blood flow and circulatory resistance of the organs were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1971
1971
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…toxic components liberated from the traumatized tissues have not been proved to be an important cause of shock. Possibly, toxins and procoagu lants are liberated from ischaemic tissues [6,20], More attention has been paid to hypovolaemia produced after the release of the tourniquet [4,17,37]. In the remainder of this article, we compare the ultrastructural changes found in the kidneys in tourniquet shock with those produced by other types of shock and draw conclusions about the pathogenesis of the former.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…toxic components liberated from the traumatized tissues have not been proved to be an important cause of shock. Possibly, toxins and procoagu lants are liberated from ischaemic tissues [6,20], More attention has been paid to hypovolaemia produced after the release of the tourniquet [4,17,37]. In the remainder of this article, we compare the ultrastructural changes found in the kidneys in tourniquet shock with those produced by other types of shock and draw conclusions about the pathogenesis of the former.…”
Section: Discussionmentioning
confidence: 99%
“…The oedema in the limbs decreases the circulating blood volume; cardiac output is de creased by two thirds and renal perfusion by three quarters of normal [37]. A llen [4] showed that injections of physiological saline can resusci tate the animals from tourniquet shock.…”
Section: Introductionmentioning
confidence: 99%
“…From the values of cardiac output, blood pressure, organ weights and fractions of cardiac output, organ blood flow and vascular resistance were calculated for 100 g tissue; the total peripheral resistance was also calculated (Sapirstein, 1958;Takacs et al, 1962). Alterations in blood pressure and cardiac output in the range occurring in these experiments did not modify the extraction rate of 'Rb from the blood (Takacs, Kallay & Karai, 1964).…”
Section: Methodsmentioning
confidence: 98%
“…The method using the fractional distribution of indicators (Sapirstein, 1956(Sapirstein, , 1957(Sapirstein, , 1958 was of value in estimating regional distribution of the cardiac output and has been widely used in our laboratory (Takacs, Kallay & Skolnik, 1962;Takacs & Vajda, 1963;Takacs, 1965). It was shown that pronethalol (10 mg/kg) had only slight circulatory effects in rats while the effects of dichloroisoprenaline (10 mg/kg) were mostly due to its sympathomimetic activity (Debreczeni & Takacs, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…It is also indicated that carotid baroreceptor unloading had no effect on skin blood flow in humans [6]. On the other hand, there is literature demonstrating that hemorrhaging is clearly associated with cutaneous vasoconstriction through sympathetic activation in mice [7], rats [8][9][10][11], rabbits [12,13], and dogs [14]. However, its mechanism for hemorrhage-induced skin vasoconstriction still remains controversial.…”
mentioning
confidence: 99%